Literasi Baca Tulis Anak-Anak dan Remaja Karang Taruna Puspasari Sanggarahan, Canden, Jetis, Bantul - Nur Alifah Septiani; Kusnul Fitria (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The pandemic is making progress with the propensities for kids and youngsters. Before the pandemic, kids and teens played seriously or looked sickened, yet these exercises have become uncommon since the pandemic. This is a direct result of exercises outside the room or in the public region. Kids and young people since the pandemic have become dynamic on the internet due to requests for BDR. These exercises in a roundabout way lead kids and teenagers to strongly utilize virtual entertainment more. This new leisure activity diminishes kids' and youth's advantage in perusing and composing. This should be visible from the capacity of kids and youth at Karang Taruna Puspasari to communicate their creative minds written down. Composing is one stage to figure out how far somebody has information. The preparation exercises the Community Service Team did are the first move toward quite a while and youths to cherish perusing and composing. Perusing and composing can level up the skill to think imaginatively and open up skylines so the more youthful age of Indonesia turns into a brilliant and innovative age.